Sustainable customer solutions: an institutional theory approach to link resource integration and value creation. - Widmer, Tobias (Cranfield University, 2023)
Alternatives to current resource intensive ways of production and consumption are required to achieve the UN Sustainable Development Goals. Transitioning from product sales to providing customer solutions (CS) has the potential to enhance sustainability. This transition, however, leads to managerial complexity, which increases further when trying to simultaneously become more sustainable. To succeed, manufacturers must ensure that their customers create economic, social, and environmental value with the CS. However, pursuing multiple goals may lead to tensions or require trade-offs. Informed by literature from Institutional Theory, industrial marketing, and sustainability, two studies were conducted. First, a multiple-case study investigated under which conditions resource integration (RI) is sustainable. By using ideal type logics, the study identified practices, values, and beliefs of business logics, as well as occurrences of conflicting, competing, and compatible logics which must be navigated collaboratively with customers to overcome barriers. Second, a single-case study investigated how RI translates into customers achieving their economic, social, and environmental goals. The study identified resources, value proposition components, and value-in-use constructs which were used in a means-end chain analysis, identifying multiple internal and external enablers and catalysts to stewardship practice in CS. The study found that CS can enhance sustainability compared to product sales, though it is not inherently guaranteed. The development of value propositions (VP) in CS is triggered internally or through the customers. Customers’ goals and the assessment thereof are continuously changing, requiring the VP to be dynamic and adapting by introducing and removing resources. A proposed framework of a value creation cycle establishes stewardship practice as a means to empirically explore and theoretically explain value creation in sustainable CS with institutional arrangements that manifest at multiple levels of a service-ecosystem. Along the value creation cycle, novel operational and cultural enablers and catalysts as well as challenges were identified, and are added to the body of knowledge which helps managers understand the requirements for successfully developing and implementing sustainable CS.
Prior, Daniel - Associate Supervisor Aktas, Emel - Associate Supervisor
Keywords: Value proposition development; stewardship practice; circular economy; sustainability; business logics; barriers